Analysis of Gaze Behavior to Measure Cognitive Distraction in Real-World Driving. (September 2018) - Yang, Shiyan; Kuo, Jonny; Lenné, Michael G.
Cognitive distraction can impair drivers' situation awareness and control performance in driving. An on-road study was conducted to examine the efficacy in the detection of driver cognitive distraction based on the driver monitoring system developed by Seeing Machines. Participants completed a 25-km test drive on the local public roads whilst engaging in a series of secondary tasks that were designed to trigger different types of cognitive distraction, such as conversation, comprehension, N-back, and route-planning tasks. The findings showed that percent road center (PRC), one of the promising gaze metrics, increased significantly with cognitive distraction when compared to baseline, but failed to distinguish between different forms of cognitive distraction Moreover, PRC's sensitivity to cognitive distraction was found to be affected by the chosen radius of road center area. These findings of driver cognitive distraction measurement provide data-driven suggestions for the development of real-time driver monitoring systems in the wild.